Soy-isoflavone supplementation tends to reduce menopausal symptoms in postmenopausal women - Raditya Wratsangka; Atut Cicih Mayasari (Universa Medicina, 2013)
BACKGROUNDMenopausal symptoms in postmenopausal women tend to decrease healthrelated quality of life (HRQoL). The present study’s objective was to determine the effect of daily supplementation of 100 mg soy isoflavones on menopausalsymptoms of healthy postmenopausal women. Isoflavones are phytoestrogens abundantly found in soy beans, and several studies have demonstrated that isoflavones are the best among the phytoestrogens.METHODSThe study was a community-based double blind randomized controlled trial involving 60 healthy postmenopausal women, aged between 48–60 years, in the Mampang Prapatan District, South Jakarta. Participants were block-randomized to receive either 100 mg soy-isoflavone + 500 mg calcium carbonate (intervention group) or 500 mg calcium carbonate only (control group). Both supplements were taken daily for 12 weeks, from January to April 2010. Menopausal symptoms(measured by Menopause Rating Scale questionnaire) were assessed at baseline and after supplementation. Chi-square test was used to examine the effect of soy isoflavone supplementation on menopausal symptoms.RESULTSFifty-six (93.3%) of participants completed the study. There were no statistically significant differences (p>0.05) in the prevalence of menopausal symptoms between the isoflavone group and the control group. However, supplementationof soy isoflavones for 12 weeks tended to decrease the prevalence of menopausal symptoms in women with normal body mass index and adequate daily dietary isoflavone intake.CONCLUSIONDaily supplementation of 100 mg soy isoflavones for 12 weeks tend to decrease the incidence of menopausal symptoms in postmenopausal women.